Предмет: Математика, автор: Arhangel111

Пррошу омогите даю 1100 баллов

Приложения:

Ответы

Автор ответа: IrkaShevko
1

Ответ:

0

Пошаговое объяснение:

\lim_{x \to 0} (ctgx - \dfrac{1}{x} )= \lim_{x \to 0} (\dfrac{cosx}{sinx} - \dfrac{1}{x} )= \lim_{x \to 0} (\dfrac{xcosx-sinx}{xsinx} )=[\frac{0}{0} ]=\\\\= [sinx->x]= \lim_{x \to 0} (\dfrac{xcosx-sinx}{x^2} )=\lim_{x \to 0} (\dfrac{cosx-xsinx-cosx}{2x} )=\lim_{x \to 0} (\dfrac{xsinx}{2x} )=\lim_{x \to 0} (\dfrac{sinx}{2} )=0

Похожие вопросы